Knowledge-based enterprise theories and fundamentals - Wickramasinghe (Idea Group Pub., 2007)
"This book provides comprehensive coverage of all areas (people, process, and technology) necessary to become a knowledge-based enterprise. It presents several frameworks facilitating the implementation of a KM initiative and its ongoing management so that pertinent knowledge and information are always available to the decision maker, and so the organization may always enjoy a sustainable competitive advantage"--Provided by publisher